Error Analysis on the Students’ English Speech of Stmik Sinar Nusantara - Suryanti Galuh Pravitasari; Saly Kurnia Octaviani; Arumsari (Faculty of Language and Literature, University of Surakarta, 2021)
This research was aimed at finding out the student’s English speech errors of STMIK Sinar Nusantara using psycho-linguistic approach. This study belongs to the qualitative descriptive research with 30 respondents selected by using simple random sampling. The data were collected by recording the students’ presentation. After that the data were analyzed by conducting observation and classification the errors found in the respondents’ speech using psycho-linguistic approach proposed by Clark and Clark. The result of the study showed that there were 336 (100%) speech errors found which were than classified into Silent Pause (34%), Filled Pause (13.7%), Repeats (9.2%), Retraced False Start 0.3%), Corrections (4.5%), Interjections (3.7%), Stutters (14%), dan Slip of Tongue (20.1%).